Water retention in a peatland with organic matter in different decomposition stages - Rocha Campos,José Ricardo da (2011)
Peatlands are ecosystems formed by successive pedogenetic processes, resulting in progressive accumulation of plant remains in the soil column under conditions that inhibit the activity of most microbial decomposers. In Diamantina, state of Minas Gerais, Brazil, a peatland is located at 1366 m asl, in a region with a quartz-rich lithology and characteristic wet grassland vegetation. For this study, the peat area was divided in 12 transects, from which a total of 90 soil samples were collected at a distance of 20 m from each other. The properties rubbed fiber content (RF), bulk density (Bd), mineral material (MM), organic matter (OM), moisture (Moi) and maximum water holding capacity (MWHC) were analyzed in all samples. From three selected profiles of this whole area, samples were collected every 27 cm from the soil surface down to a depth of 216 cm. In these samples, moisture was additionally determined at a pressure of 10 kPa (Moi10) or 1500 kPa (Moi1500), using Richards' extractor and soil organic matter was fractionated by standard procedures. The OM decomposition stage of this peat was found to increase with soil depth. Moi and MWHC were highest in layers with less advanced stages of OM decomposition. The humin levels were highest in layers in earlier stages of OM decomposition and with higher levels of water retention at MWHC and Moi10. Humic acid contents were higher in layers at an intermediate stage of decomposition of organic matter and with lowest levels of water retention at MWHC, Moi10 and Moi1500.